Eels : the superpower field guide - Poliquin, Rachel, 1975- (Poliquin, Rachel, 1975- Superpower field guide., 2020)
"Emergent readers will dive right into this search-and-find book about eels. Simple text and colorful underwater photos teach new vocabulary and facts on anatomy, markings, and ocean habitat"--